Current state-of-the-art and potential future therapeutic drugs against COVID-19 - Sha, Ailong; Liu, Yi; Hao, Haiyan (Frontiers in Cell and Developmental Biology, 2023)
The novel coronavirus disease (COVID-19) continues to endanger human health, and its therapeutic drugs are under intensive research and development. Identifying the efficacy and toxicity of drugs in animal models is helpful for further screening of effective medications, which is also a prerequisite for drugs to enter clinical trials. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) invades host cells mainly by the S protein on its surface. After the SARS-CoV-2 RNA genome is injected into the cells, M protein will help assemble and release new viruses. RdRp is crucial for virus replication, assembly, and release of new virus particles. This review analyzes and discusses 26 anti-SARS-CoV-2 drugs based on their mechanism of action, effectiveness and safety in different animal models. We propose five drugs to be the most promising to enter the next stage of clinical trial research, thus providing a reference for future drug development.